Disciplinary English reform and practices of undergraduate program in response to cultivation of interdisciplinary elites in China - Nana Zhou (Humanities & Social Sciences Communications)
Abstract Disciplinary English was proposed as a new pedagogical approach of English educational reform under the heading of New Liberal Arts which requires to restructure the knowledge of Liberal Arts to cultivate interdisciplinary elites for the socioeconomic development in China. The article aims to illustrate disciplinary English’s implications, its distinction from ESP, EMI and CLIL, its prevalent theories and its implicit resistance against English’s hegemony in pedagogical practices of undergraduate program in China. The article adopts case study and reflectivity approach to illustrate how China’s New Liberal Arts responded to English’s dominance in foreign language education by implementing disciplinary English reform. The discussion shows that the interdisciplinary practices of disciplinary English were rooted in Chinese culture, aligned with the interdisciplinary requirement of English educational reform of New Liberal Arts, and featured the cooperation with the local socioeconomic enterprises. As a new pedagogical approach, disciplinary English is faced with the challenges in practices, such as the intersection between English and disciplinary knowledge and the ideological and cultural share in teaching and learning activities. The results provide a lens for the further explanation of disciplinary English and other pedagogical practices of English educational reform at the universities in China and other non-English speaking countries.